Microteaching Frequency and the Development of Teaching Skills and Pedagogical Content Knowledge among Prospective Mathematics Teachers - Raden Rosnawati; Ariyadi Wijaya; Tuharto Tuharto; Caturiyati Caturiyati; Mariano Dos Santos (Jurnal Pendidikan MIPA, 2025)
The teaching skills developed by prospective teachers are often repeated in different situations. Therefore, the optimal frequency of microteaching practices may influence both teaching skills and pedagogical content knowledge. This study used a cross-sectional design to compare teaching skills and pedagogical content knowledge among groups based on the frequency of microteaching practices conducted by prospective mathematics teachers. A total of 79 students were randomly selected from three universities in Yogyakarta that implemented microteaching with varying frequencies. These frequencies were classified into four categories: once, twice, three times, and more than three times. Teaching skills were assessed using observation sheets that outlined aspects such as explaining skills, asking questions, providing guidance, providing reinforcement, managing whiteboard use, and regulating body movement (non-verbal cues). Pedagogical content knowledge was measured using a test instrument. Data were analyzed using descriptive statistics and a one-way ANOVA test. The results showed that the frequency of practice has a different impact on teaching skills and pedagogical content knowledge. Prospective teachers who practiced microteaching more than three times significantly differed in their explaining skills, while their providing reinforcement differed significantly from those who practiced at least three times. Conversely, prospective teachers who practiced twice performed similar levels of skill in asking questions, whiteboard management, and regulating body movement compared to those who practiced more frequently. Pedagogical content knowledge of prospective teachers who practiced more than three times was significantly higher than that of those who practiced three or fewer times. These findings suggest that universities should carefully regulate the frequency of microteaching practices to optimize students' teaching skills and pedagogical content knowledge in mathematics education for those who aspire to become effective mathematics teachers. These findings suggest that universities should carefully regulate the frequency of microteaching practices to optimize students' teaching skills and pedagogical content knowledge in mathematics education students who aspire to become effective mathematics teachers.    Keywords: teaching skills, microteaching, mathematics.